PRINSIP-PRINSIP DAKWAH MENURUT SAYYID QUTHUB (Sebagai Pedoman Dai Untuk Keberhasilan Dakwah) - Muhammad Anwar (Fakultas Dakwah dan Komunikasi, 2015)
Da'wah is an invitation to a life that is more graceful form of life that is able to actualize Islamic moral values in various forms, are also able to appreciate the whole meaning to the reality of life more humane. By him that every missionary activity should be designed and carried out as well as possible by taking into account various situations and conditions encountered. Furthermore, how the propaganda should be done, of course, using the methodology of da’wa which is one aspect that is very important in the process of da’wa.Methodology da’wa no less important than da’wa material itself. In speaking of this da’wa methodology includes at least three main topics namely; general rule the da’wa of Islam, the principles of the methodology of da’wa and proselytizing movement system. All three of the above are interrelated to one another. And need to be translated into a system of da’wa movement that is more technical and operational. To achieve success dai in activities teachings, then they must be necessary to establish an organization that serves as an institution or the container will collect and menytukan potential and power of the people to be exploited and empowered for progress and success dai, meaning that missionary activity is no longer seen as a task individual duty, but it is a collective duty and obligation of all Muslims, because the problem is so severe da’wa, the da’wa collective dikooordinasi by an institution that is strong and solid preaching, is seen as an absolute requirement for success preaching the da’i.